Effect of School Feeding Programme on Primary Education in Ijebu-Ode Local Government Area of Ogun State, Nigeria (2010-2020) - Atobatel, Abolaji Jamiu; Okewale, Raheem Akanni (Covenant University Journal of Politics and International Affairs, 2021)
Hunger has grave impact on education and health status of the children that is the major reason the international organizations such as United Nations Educational, Scientific and Cultural Organization (UNESCO), Food and Agriculture Organization (FAO), United Nations International Children’s Emergency Funds (UNICEF), World Bank and other stakeholders are making herculean efforts to ensure that the spate of hunger is reduced in the world. Also it is unfortunate that the spate of hunger is a common phenomenon in the developing countries despite the fact that most of these developing countries are agrarian. Therefore increase in hunger affects pupils enrollment, retention etc. In order to encourage the education of the children in Nigeria, the federal government through the State and Local government initiated a home grown feeding programme in all the States of the federation. However, it is against this backdrop that this study examines the effect of school feeding programme on educational system in Ijebu-Ode Local Government Area of Ogun State. The study relied on primary source with the use of questionnaire and interview to gather information from the respondents in Ijebu-Ode Local Government Area. Partial Least Square technique was used to analyse the data garnered from the field. The study revealed that home grown school feeding programme does not have effect on Educational system in Ijebu-Ode except it is accompanied with massive infrastructure. Also government and the stakeholders should ensure that this programme is monitored to letter so that low quality food will not be served to the pupils.